The Effectiveness of Emotion-Focused Therapy on Job Stress and Emotion Regulation in Employed Women in Tonekabon - Arjmandi, Nadia; Sadeghi, Elaheh; Tarkhan, Morteza (Psychology of Woman Journal, 2025)
Objective: The present study aimed to investigate the effectiveness of Emotion-Focused Therapy (EFT) on job stress and emotion regulation in employed women.Methods and Materials: This quasi-experimental research employed a pre-test–post-test design with a control group. The statistical population consisted of all employed women in Tonekabon in 2025. The research sample included 30 participants selected through purposive sampling, who were then randomly assigned to an experimental group (n = 15) and a control group (n = 15). Research instruments included the Job Stress Questionnaire developed by the UK Health and Safety Executive (1990) and the Emotion Regulation Questionnaire (Gross & John, 2003). Multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA within MANCOVA) were used for data analysis.Findings: The results indicated a statistically significant difference between the experimental and control groups in the post-test regarding the mean scores of job stress and emotion regulation (p < .001); specifically, Emotion-Focused Therapy led to a reduction in job stress and an increase in emotion regulation among employed women.Conclusion: The findings favored the experimental group. Overall, the results indicated that Emotion-Focused Therapy led to a reduction in marital stress and an improvement in behavioral emotion regulation among married women.